CLINICAL STUDY TO EVALUATE THE EFFICACY OF NAVAKARSHIKA KWATHA FOR THE TREATMENT OF SHITAPITTA - *Manish M. Kanhed; Vivek Chandurkar (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda gives basic guidelines for the healthy wellbeing and treatment of disease if occurred. Shitapitta is disease occurring commonly and presenting as itchy red patches all over the body, fever and redness of eyes. Though the condition is not life threatening but it has its routine disturbing impact. Many of antihistaminic agents show instant effect on the disease condition but frequent relapse occurs. This frequency of relapse made this study to happen for eradication of the root cause of disease. Hence Navakarshika kwatha (decoction prepared with 9 herbal medicines) used for the disease treatment to evaluate its efficacy. Navakarshika Kwatha was given in dose of 20ml twice a day immediately after meals to 30 patients. Follow-up of the patients was kept after every 7 days for 28 days. During each follow-up signs and symptoms were noted with multidimensional scoring system. The causative factors for the disease according to classics were advised to exempt to achieve the Nidanparivarjana. Type of study was plain and paired t test was applied on the data of these 30 patients before and after treatment. After comparing the signs and symptoms with multidimensional scoring system before and after the treatment excellent results (above 80%) were found in 11 patients and moderate results were observed in 19 patients.